PREVALENCE OF SOFT DRINK AND HEALTHY FOOD CONSUMPTION AMONG FEDERAL EDUCATION NETWORK EMPLOYEES (CIPEEX, 2025)
Introduction: The consumption of ultra-processed foods has increased and has been linked to adverse health effects. In contrast, a diet based on fresh or minimally processed foods contributes to disease prevention. Analyzing these eating behaviors is essential for developing effective health promotion policies and strategies. Objective: Associating regular consumption of soft drinks and healthy foods among employees of the Federal Network for Professional, Scientific, and Technological Education (RFEPCT). Method: This cross-sectional epidemiological study employed a quantitative approach and was carried out in November 2022 after receiving approval from the Research Ethics Committee (protocol number 5,270,596). The sample consisted of 1,563 RFEPCT professionals, including teachers and TAE. Sociodemographic variables and the PeNSE questionnaire were analyzed. Consumption of sweets or healthy foods on ≥5 days per week was considered regular (CR), while consumption on ≤4 days per week was considered irregular (CI). The effect measure used was the prevalence ratio (PR) with 95% confidence intervals (CIs). Results: Soft drink consumption rate (CR) was positively associated with the Southeast (p = 0.002) and Midwest (p = 0.001) regions and negatively associated with the 48–60 age group (p = 0.020). We also observed a positive association with FR consumption of fresh fruit (p < 0.001). There were no associations found with female gender (p = 0.790), teaching position (p = 0.108), or consumption of vegetables (p = 0.054). Conclusion: The results suggest that the dietary profile of RFEPCT employees may be influenced by sociodemographic factors. This evidence underscores the importance of initiatives that promote healthy habits in institutional settings, focusing on equity and improving health conditions at work.